Principals' Administrative Strategies for School Effectiveness in Secondary Schools in Yobe State - Garba, Umar (NIU Journal of Social Sciences, 2019)
This study examined principals' administrative strategies for school effectiveness in secondary schools in Yobe State. Specifically, the study investigated the opinions of teachers on principals' administrative strategies for school effectiveness. Three research questions guided the study. This study adopted a descriptive survey research design. The population of the study consisted of teachers in all secondary schools in Yobe State. The sample consisted of three hundred and eighty-eight (388) teachers. The instrument used for the study was questionnaire titled: Principals' Administrative Strategies for School Effectiveness in Secondary Schools (PASSE). Frequency count and percentages were used in analyzing the collected data. The findings of the study revealed that instructional supervision by principals were not carried out fairly; principals' leadership style were more of autocratic and laissez-faire which could affect the school effectiveness among others. Based on the findings, it was recommended among others, that principals should adopt suitable leadership style that could promote school effectiveness. Keywords: Principal, Administrative, Strategies, School, Effectiveness